TATA KELOLA DANAU BAKUOK BERBASIS KEARIFAN LOKAL DI DESA AUR SATI KECAMATAN TAMBANG KABUPATEN KAMPAR - Neneng Winarta; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Local wisdom is a form of wisdom that is based on the values of goodness that are trusted, applied and always maintained in a long period of time from generation to generation by a group of people in a particular area or area that is their place of residence. On Lake Bakuok there is a form of local wisdom in the form of lubuk prohibition and Maawuo annual event. In this lake is prohibited from catching fish carelessly when the lake has been topped. Lake Bakuok is managed systemically by ninik mamak. The management of Lake Bakuok has a goal to lift the economy of the community and then wants to change the system of life in the middle of the community, and make the village a tourist destination and become an annual event on the tourist calendar at the provincial and national levels. The theory used in this study is Sagala which has 3 stages of actuating, namely directing, communicating and coordinating. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The selection of research informants used the snowball sampling technique. The results of this study indicate that there are inhibiting factors in the management of Lake Bakuok in Aur Sati village, Tambang District, Kampar Regency. These factors are a lack of community participation and budget.Keywords: Governance, Lake, Local Wisdom